Residence Time, a New parameter to Predict Neurosteroidogenic Efficacy of Translocator Protein (TSPO) Ligands: the Case Study of N, N‐Dialkyl‐2‐arylindol‐3‐ylglyoxylamides. (22nd June 2017) - Costa, Barbara; Taliani, Sabrina; Da Pozzo, Eleonora; Barresi, Elisabetta; Robello, Marco; Cavallini, Chiara; Cosconati, Sandro; Da Settimo, Federico; Novellino, Ettore; Martini, Claudia
Abstract: Targeting the biosynthetic pathway of neuroactive steroids with specific 18 kDa translocator protein (TSPO) ligands may be a viable therapeutic approach for a variety of neurodegenerative and neuropsychiatric diseases. However, the lack of correlation between binding affinity and in vitro steroidogenic efficacy has limited the identification of lead compounds by traditional affinity‐based drug discovery strategies. Our recent research indicates that the key factor for robust steroidogenic TSPO ligand efficacy is not the binding affinity per se, but rather the time the compound spends in the target, namely its residence time (RT). The assessment of this kinetic parameter during the in vitro characterization of compounds appears mandatory in order to obtain structure–efficacy relationships suitable for the future development of novel molecules with promising pharmacological properties. Abstract : How long can you stay? The neurosteroidogenic efficacy of translocator protein (TSPO) ligands can be predicted by evaluating the amount of time—the residence time—that a given ligand spends in the target rather than the binding affinity. This aids in the development of novel compounds with promising pharmacological properties and therapeutic potential.